2014
DOI: 10.1155/2014/387070
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Symptomatic Vulvovaginal Candidiasis among Human Immunodeficiency Virus Type 1 Infected Women in Rural KwaZulu-Natal, South Africa

Abstract: Introduction. We sought to determine the association between HIV-induced immunosuppression, virologic correlates, and vulvovaginal candidiasis (VVC). Methods. This is a retrospective cohort study, where HIV infected and uninfected women were studied with VVC being the primary outcome. Ninety-seven HIV-infected and 101 HIV-uninfected women were enrolled between June and December 2011. Cases of VVC were confirmed. HIV RNA load was determined by RT-PCR and CD4 counts were obtained from medical records. Results. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
2
12
2
1
Order By: Relevance
“…Trichomoniasis is considered to be the most prevalent nonviral sexually transmitted infection (STI) worldwide affecting individuals of all ages, ethnicity, and socioeconomic groups [ 2 , 3 ]. The global prevalence rates for T. vaginalis varies between 0.9% and 80% [ 14 – 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trichomoniasis is considered to be the most prevalent nonviral sexually transmitted infection (STI) worldwide affecting individuals of all ages, ethnicity, and socioeconomic groups [ 2 , 3 ]. The global prevalence rates for T. vaginalis varies between 0.9% and 80% [ 14 – 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is likely to be the results of mucosal barrier disruption and/or inflammation associated with vulvovaginal candidiasis. Seventy-five percent of women experience at least one episode of candidiasis during their life, and the risk for frequent, more invasive and resistant infections in persons living with HIV is high, likely due to T cell immune defects [50]. Other in vitro studies have shown that HSV-2 significantly enhances binding of Candida albicans to HeLa cells [51], which the authors conclude suggests that HSV-2 increases Candida persistence in the FGT.…”
Section: Interactions Between the Viral And Fungal Microbiotamentioning
confidence: 90%
“…Although vulvovaginal candidiasis occurs more frequently in HIV-infected women than in HIV-uninfected women, [50] most SA studies are cross-sectional and not longitudinal, and therefore do not inform the incidence of recurrence. [50,51] Based on international data, [52,53] we conservatively assumed that recurrent vulvovaginal candidiasis -defined as ≥4 episodes per year -had a prevalence of 6% among females aged 15 -54 years; this risk was not adjusted for HIV status.…”
Section: Researchmentioning
confidence: 99%